2021
DOI: 10.1590/0100-6991e-20202704
|View full text |Cite
|
Sign up to set email alerts
|

Robotic TAPP inguinal hernia repair: lessons learned from 97 cases

Abstract: Objectives: minimally invasive inguinal hernia repair has proven advantages over open procedures including less pain and earlier return to normal activity. Robotic surgery adds ergonomics, a three-dimensional high definition camera and articulating instruments overcoming some laparoscopic limitations. We aimed to report the outcomes of the early experience of over 97 robotic inguinal hernia repairs performed by a referred surgical group in Brazil. Methods: a review of a prospective mantined database was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…[ 18 ] Several articles have reported relatively long operation times but low postoperative complication rates and pain levels associated with robotic inguinal surgery. [ 16 , 17 , 19 , 20 ] The Da Vinci Xi system dramatically reduced robot docking time compared with the previous Si system. In our study, the actual docking time was about 2 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] Several articles have reported relatively long operation times but low postoperative complication rates and pain levels associated with robotic inguinal surgery. [ 16 , 17 , 19 , 20 ] The Da Vinci Xi system dramatically reduced robot docking time compared with the previous Si system. In our study, the actual docking time was about 2 min.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 , 13 , 14 ] The first report of robot-assisted hernia surgery was of a repair performed together with urologic procedures in 2014, and Dominguez et al reported the first robotic hernia surgery results. [ 1 , 15 ] Since then, robotic hernia surgery has been reported to reduce postoperative pain and facilitate ergonomic optimization for surgeons, and it has been attempted and adopted by surgeons worldwide [ 1 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 In a standardized operating setting, a camera port is inserted into the abdominal cavity after umbilical access and two 8-mm robotic ports are placed either side lateral to the umbilicus, slightly above or below the umbilical line, with a minimum of 10 cm lateral to the supraumbilical port and 10 cm superior to the anterior superior iliac spine. 15,16 Similarly, the operating setting for the robotic transabdominal retromuscular umbilical prosthetic hernia repair (TARUP) technique is performed in a standard way by the robotic surgeons:…”
Section: Discussionmentioning
confidence: 99%
“…Transabdominal preperitoneal (TAPP) approach has gained space so the preperitoneal space has started to be endorsed in minimally invasive inguinal hernia repair 14 . In a standardized operating setting, a camera port is inserted into the abdominal cavity after umbilical access and two 8‐mm robotic ports are placed either side lateral to the umbilicus, slightly above or below the umbilical line, with a minimum of 10 cm lateral to the supraumbilical port and 10 cm superior to the anterior superior iliac spine 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Technology has rapidly advanced in the field of surgery especially in the past 10 years, which is thought to progress even more in the near future. Robots have increasingly gained popularity and would be the future of surgery according to some authors [27]. Considering the rapidly growing industry and the huge progress made in the field of artificial intelligence, it is difficult to keep oneself updated with the recent advances.…”
Section: Robotic Surgical Systems and Future Directionsmentioning
confidence: 99%